2020
DOI: 10.1155/2020/3082318
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Uric Acid and Bone Mineral Density in Older Adults

Abstract: Objectives. Uric acid has been found to be potentially protective in bone metabolism. We investigated the relationship between serum uric acid (sUA) and lumbar bone mineral density (BMD) among 4156 participants aged 60 years and over from the National Health and Nutrition Examination Survey (NHANES). Methods. To estimate the association between sUA and lumbar BMD, multivariate logistic regression analyses were conducted. Fitted smoothing curves and generalized additive models were also performed. Results. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…The study also confirmed no significant association between SUA and total body BMD in young adults, women, non-obese, and smokers. This finding is supported by several epidemiological studies using different study designs and population samples (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) as listed in Table 2. These epidemiological studies aimed to elucidate the relation between SUA and bone health.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The study also confirmed no significant association between SUA and total body BMD in young adults, women, non-obese, and smokers. This finding is supported by several epidemiological studies using different study designs and population samples (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) as listed in Table 2. These epidemiological studies aimed to elucidate the relation between SUA and bone health.…”
Section: Discussionsupporting
confidence: 63%
“…Consistently two longitudinal studies had concluded the positive association between SUA and annual rates of change in BMD at different skeletal sites ( 31 ) and lower risk in developing osteoporotic fractures ( 29 ). Interestingly, other studies had additionally confirmed the lack of association between SUA and BMD in young females ( 35 ) and black Americans ( 34 ).…”
Section: Discussionmentioning
confidence: 89%
“…At the hydrophilic condition, it shows the protective effects of antioxidants [38]. Reducing SUA could decline its protective effect to radiation damage [39], and total bone mineral density [40,41] or a protective effect on bone loss in rheumatoid arthritis [42] ( Figure 1). Beyond its role in protection, over-saturated SUA together with sodium could deposit in joints, soft tissues, bones, skin, etc., as MSU crystals to form tophi and trigger gout flares with episodes of severe pain.…”
Section: Uric Acid and Goutmentioning
confidence: 99%
“…At the hydrophilic condition, it shows the protective effects of antioxidants [ 38 ]. Reducing SUA could decline its protective effect to radiation damage [ 39 ], and total bone mineral density [ 40 , 41 ] or a protective effect on bone loss in rheumatoid arthritis [ 42 ] ( Figure 1 ).…”
Section: Uric Acid and Goutmentioning
confidence: 99%
“…At the hydrophilic condition, it shows the protective effects of antioxidant [38]. Reducing SUA could decline the protecting effect to radiation damage [39], and total bone mineral density [40,41] or a protective effect on bone loss in rheumatoid arthritis [42].…”
Section: Uric Acid and Goutmentioning
confidence: 99%